SISTEM PEMBUKA PINTU OTOMATIS SAFE DEPOSIT BOX PADA BANK - Naga, Dali S.; Utama, Hadian S.; Sudimanto, Sudimanto (TESLA Jurnal Teknik Elektro UNTAR, 2008)
Service of Safe Deposit Box is depository box rent service. The securities designed peculiarly from substance become militant and placed in sturdy space khasanah, hold up to unload and flame resistant to give the safety for its owner. To open the this Safe Deposit Box all owner of this Safe Deposit Box have to own the key got at the time of first time own the Safe Deposit Box. Opening of Door of Safe Deposit Box conducted in manual. One of way there is a system which can open the Safe Deposit Box automatically, by using Magnetic card and PIN which input on keypad.